2019
DOI: 10.1515/cllt-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Entrenchment and persistence in language change: the Spanish past subjunctive

Abstract: In this paper, we demonstrate that, like frequency, morphosyntactic persistence can have a conserving effect on language change. To substantiate this claim, we analyze the alternation between the Spanish past subjunctive forms ending in –ra and –se (as in comiera and comiese ‘had eaten’). Due to the ongoing replacement of –se by –ra, persistence and frequency are the best predictors of the alternation in our data. First, the persistence effect of a prior –se is significantly greater than the persistence effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…It has been repeatedly demonstrated that less frequent constructions engender stronger persistence effects than more frequent constructions do (e.g. Bock 1986, Ferreira 2003, Rosemeyer & Schwenter 2017. We submit that persistence and mood choice represent two disparate phenomena exhibiting disparate characteristic features.…”
Section: Theoretical Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It has been repeatedly demonstrated that less frequent constructions engender stronger persistence effects than more frequent constructions do (e.g. Bock 1986, Ferreira 2003, Rosemeyer & Schwenter 2017. We submit that persistence and mood choice represent two disparate phenomena exhibiting disparate characteristic features.…”
Section: Theoretical Discussionmentioning
confidence: 66%
“…Note further that the two phenomena have different time windows. For example, Rosemeyer & Schwenter (2017) observed persistence effects over stretches of as many as 100 words. This is much more than the (average or maximum) distance between trigger and target in our data.…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…Lexical subjects, on the contrary, are rather infrequent in the context of the task. Schwenter and colleagues have argued that forms that are less frequent show a stronger perseveration effect (Rosemeyer and Schwenter 2017;Schwenter and Cacoullos 2008;inter alia). Thus, it is possible that the oddity of the use of lexical subjects in the context of a story with only one human referent may have made lexical subjects, in addition to being infrequent, more salient, and, thus, a better target for perseveration.…”
Section: Discussionmentioning
confidence: 99%
“…Torres Cacoullos's study offers a promising method to test whether underlying structures can become gradually less analysable over time. Crucially, it also shows that priming effects can be studied and exploited to make a theoretical point even in historical written data (see also Rosemeyer & Schwenter 2017).…”
Section: Degrees Of Structurementioning
confidence: 98%